2016
DOI: 10.1038/srep39486
|View full text |Cite
|
Sign up to set email alerts
|

A Magnetic Soft Endoscopic Capsule-Inflated Intragastric Balloon for Weight Management

Abstract: Overweight and obesity have been identified as a cause of high risk diseases like diabetes and cancer. Although conventional Intragastric Balloons (IGBs) have become an efficient and less invasive method for overweight and obesity treatment, the use of conventional tools such as catheter or endoscope to insert and remove the IGBs from the patient’s body causes nausea, vomiting, discomfort, and even gastric mucous damage. To eliminate these drawbacks, we develop a novel magnetic soft capsule device with gas-fil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 50 publications
0
18
0
Order By: Relevance
“…Do et al developed a gas-filled spherical balloon with a magnetic soft capsule device [ 43 ]. The magnetic capsule is controlled by an external magnetic field to open the inflation and deflation valves.…”
Section: Balloons Under Developmentmentioning
confidence: 99%
“…Do et al developed a gas-filled spherical balloon with a magnetic soft capsule device [ 43 ]. The magnetic capsule is controlled by an external magnetic field to open the inflation and deflation valves.…”
Section: Balloons Under Developmentmentioning
confidence: 99%
“…[194][195][196][197] To implement the magnetic actuation in surgical tools, magnetic generators are externally located outside the patient's abdominal wall where the actuation force/torque is magnetically transmitted from outside via the abdominal wall. [198][199][200] This means that on-board electromagnetic motors or cables are eliminated. Many magnetic actuation methods have been studied for use in surgical systems.…”
Section: Advanced Actuation For Surgical Roboticsmentioning
confidence: 99%
“…d) A magnetically actuated tetherless inflatable capsule as an intragastric balloon for weight management. Reproduced with permission . Copyright 2016, Nature Publishing Group.…”
Section: Ingestible Robots For Drug Deliverymentioning
confidence: 99%
“…In addition, in vitro data suggested that the hydrogel device could also be used for ultra‐long sustained drug delivery. Inflatable capsule devices could be used for bariatric intervention . While conventional intragastric balloons are an efficient way to treat obesity, they typically require an invasive procedure using a catheter or endoscope to insert and remove the intragastric balloons from the stomach.…”
Section: Ingestible Robots For Drug Deliverymentioning
confidence: 99%